THE FUTURE OF E-COMMERCE DISPUTES: AN ANALYSIS OF MULTILATERAL DISPUTE RESOLUTION MECHANISMS - HAIJING HUANG; ONG TZE CHIN (Journal of Malaysian and Comparative Law, 2025)
The globalisation movement and the rapid growth of e-commerce necessitate effective dispute settlement mechanisms in multilateral trade agreements. The qualitative analysis conducted on the dispute settlement mechanisms in the World Trade Organization (WTO), the Association of Southeast Asian Nations (ASEAN), and the Regional Comprehensive Economic Partnership (RCEP) reveals the regulation of electronic commerce (e-commerce) and demonstrates the efforts and limits of these three trade agreements. This article compares the dispute settlement mechanisms and their legal arrangements for e-commerce within the WTO, ASEAN and RCEP frameworks to determine the most efficient for resolving e-commerce disputes in the Asian region. The results show that existing trade agreements offer a basic framework for future digital trade or e-commerce regulation, but they only provide a limited scope. The resolution of e-commerce disputes remains an ongoing issue for Member States, challenging traditional dispute settlement mechanisms and thereby requiring a new mechanism. The Online Dispute Resolution (ODR) mechanism stands out as a promising solution for the sustainable growth of e-commerce and the resolution of the surge in trade disputes.